Rancher's self-efficacy on practicing sustainable edible-nest swiflet ranching practices - K. N. Vaiappuri, Selvakkumar; Kamarulzaman, Nitty Hirawaty; Abd. Latif, Ismail; Shamsudin, Mad Nasir; Mohd Haron, Mohd Noor Hisham (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
The demand for edible-nest is increasing over the years. Ranchers as a key player in this industry plays a vital role in keeping the industry sustainable for a long term. This study was aimed to identify factors that lead to rancher’s self-efficacy on practicing sustainable practices. The study revealed five factors that associated with sustainable ranching practices. Policy makers are recommended to provide a proper attention on extension services towards implementing sustainable ranching practices to the ranchers.